PERANAN PERKEBUNAN KELAPA SAWIT TERHADAP PENGURANGAN KEMISKINAN DAN DISTRIBUSI PENDAPATAN RUMAH TANGGA DI PROPINSI RIAU - Saipul Bahri; Ujang Paman Ismail (UIR Press, 2012)
The aim of this paper was to analysis the role of oil palm plantation on poverty reduction and income distribution of farmers’ household in Riau Province. Data were collected by survey method in Kampar, Rokan Hulu, Siak and Bengkalis Regencies of Riau Province. These locations have the largest oil palm plantation area in the Province. By using multistage sampling, the total of 400 households was visited and interviewed personally in 2011. The results showed that oil palm plantation increased household income. The contribution of income received from oil palm plantation ranged from 75 to 90%. The total of income per capita of household in average was four-fold above poverty line. The per capita income from oil palm plantation only was three-fold above poverty line. Furthermore, income distribution of oil palm household was relatively equal. The development policy of oil palm plantation could increase the rural society welfare.